2019
DOI: 10.1186/s12970-019-0305-8
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent effect of caffeine supplementation on judo-specific performance and training activity: a randomized placebo-controlled crossover trial

Abstract: Background Caffeine (CAF) supplementation could have a positive impact on physical performance and sport abilities. Nevertheless, the CAF-induced, dose-dependent influence on discipline-specific performance and combat activity in combat sports have not been sufficiently investigated. The aim of this study was to examine the effect of single ingestion of 3, 6, or 9 mg/kg body weight of CAF and placebo (PLA) on judo-specific performance and sparring combat activities. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 58 publications
3
68
0
1
Order By: Relevance
“…Numerous studies have shown the effectiveness of caffeine supplementation on sports performance in which aerobic [1], anaerobic [2,3,4] or mixed [5,6,7] metabolism is prioritized. Current guidelines recommend the ingestion of low-to-moderate doses of caffeine, ranging from 3 to 6 mg/kg, approximately 60 min prior to exercise to get these improvements [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the effectiveness of caffeine supplementation on sports performance in which aerobic [1], anaerobic [2,3,4] or mixed [5,6,7] metabolism is prioritized. Current guidelines recommend the ingestion of low-to-moderate doses of caffeine, ranging from 3 to 6 mg/kg, approximately 60 min prior to exercise to get these improvements [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…SJFT) with doses between 6 and 9 mg/kg body mass, while 4 mg/kg body mass and 6 mg/kg body mass after rapid weight loss in judo did not increase significantly HR, as present results [ 2 , 15 ]. Using Edwards’ internal training load (eTRIMP) monitoring conversion [ 43 ] by measuring a product of the accumulated training duration (minute) of 5 zones by a coefficient related to each zone it is possible to suggest a dose–response relationship between training load and changes in performance associated with caffeine intake: In the present result, after the warm-up, athletes with caffeine maintained their internal load between the 3rd and the 4th zones eTRIMP (HR range 72% to 82%HR máx , with ∆ of 10%), while in placebo situation with similar training condition they had an expanded eTRIMP, using between the 3rd and 5th zones (HR mean range 69% to 90%HR máx , with ∆ of 21%) [ 7 ]. This result could be used in practical applications and future studies to understand the mechanisms involved in self-regulation during a judo championship, using caffeine and placebo conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Preceding reports [ 41 , 42 ] indicated a significant correlation between HR and RPE during a judo competition (r = 0.88, p = 0.05 ) and in a sequential simulated training with four combats ( randori ) when observed the second (r = 0.70, p = 0.05 ) and the third randori (r = 0.64, p = 0.05 ) [ 7 ]. Present results indicated similar results during randori (80–120 min) maintaining an intermittent exercise ~ 82% of HR max , classified as intense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas some studies (Astorino et al, 2008 ; Clarke et al, 2015 ; Trexler et al, 2016 ; Cesareo et al, 2019 ) reveal no significant caffeine effects on strength development, others (Anderson et al, 2000 ; Bruce et al, 2000 ; Pallarés et al, 2013 ; Behrens et al, 2015 ; Cesareo et al, 2019 ; Wilk et al, 2019 ) show significant caffeine supplementation improvements. In this context, recent studies have shown that higher doses of caffeine (above 6 mg.kg −1 ) are associated with strength and power performance improvement when compared to the use of moderate doses (Anderson et al, 2000 ; Pallarés et al, 2013 ; Durkalec-Michalski et al, 2019 ; Wilk et al, 2019 ). In these cases, the use of higher doses of caffeine could be triggering additional performance effects by increasing the calcium release from the sarcoplasmic reticulum (Klein et al, 1990 ; von Ruden and Neher, 1993 ).…”
Section: Caffeine Effectsmentioning
confidence: 99%